Math, asked by stargirl0842006, 1 year ago

Answer me.......plsplspsls​

Attachments:

Answers

Answered by Anonymous
13

{a}^{m} . {a}^{n}  \:  =  \:  {a}^{mn}

Addition if the number are in multiplication and subtract if numbers are in divisible.

Now.. the power are in multiply. So, they will add up.

=> {a}^{m\:+\:n}  \:  =  \:  {a}^{mn}

=> m + n = mn _______ (eq 1)

______________________________

• m(n - 2) + n(m - 2)

=> mn - 2m + mn - 2n

=> 2mn - 2m - 2n

=> 2mn - 2(m + n)

=> 2mn - 2(mn) [From (eq 1)]

=> 2mn - 2mn

=> 0

______________________________

m(n - 2) + n(m - 2) is 0

_________ [ ANSWER ]

______________________________

Answered by Anonymous
2

a^(m + n) = a^mn

So,

m + n = mn

Now;

m(n - 2) + n(m - 2)

mn - 2m + mn - 2n

2mn - 2m - 2n

2mn - 2(m + n)

2mn - 2(mn)

2mn - 2mn = 0

Similar questions